Edukacja tubylcza a procesy rewitalizacji etnicznej autochtonicznych mniejszości – wybrane modele i egzemplifikacje - Gmerek, Tomasz (Studia Edukacyjne, 2016)
The article deals with the issue of the relation between indigenous education and mainstream schooling in processes of autochtonous minorities ethnic revitalization. Particular emphasis was placed on reconstructing educational practices of indigenous schooling that is implemented toward indigenous minorities. An attempt was made at examining selected models of indigenous education concerning the relationship between schooling, language policy, teachers education and revitalization and development of languages, cultures, traditions and ethnic identity in contemporary multicultural societies.